2022
DOI: 10.1093/hmg/ddac162
|View full text |Cite
|
Sign up to set email alerts
|

A Mendelian randomization study to assess the genetic liability of gastroesophageal reflux disease for cardiovascular diseases and risk factors

Abstract: Observational studies have reported that gastroesophageal reflux disease (GERD) is a risk factor for cardiovascular diseases (CVD); however, the causal inferences between them remain unknown. We conducted a Mendelian randomization (MR) study to estimate the causal associations between GERD and 10 CVD outcomes, as well as 14 cardiovascular risk factors. We used summary statistics from genome-wide association studies for GERD and the FinnGen consortium for CVD. We further investigated whether GERD correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…This database includes 232,0781 single-nucleotide polymorphisms (SNPs), of which 80 are signi cantly related to GERD. According to previous studies, these SNPs can explain the 3.9% difference between the types of GERD [21]. A general F statistic greater than 10 has been reported to be robust.…”
Section: Methodsmentioning
confidence: 80%
“…This database includes 232,0781 single-nucleotide polymorphisms (SNPs), of which 80 are signi cantly related to GERD. According to previous studies, these SNPs can explain the 3.9% difference between the types of GERD [21]. A general F statistic greater than 10 has been reported to be robust.…”
Section: Methodsmentioning
confidence: 80%
“…In addition, the causality of the associations between gastroesophageal reflux disease and several CVDs was strengthened in an MR study. 34 This study also identified positive associations of gastritis and duodenitis and irritable bowel syndrome with the risk of CVD, which were explored in few studies with conflicting findings. 15,35 Future studies are warranted to confirm these associations.…”
Section: Discussionmentioning
confidence: 86%
“…Another interesting finding of our study in the stronger associations of certain gastrointestinal diseases with early-onset dementia compared to late-onset dementia. The possible reason for the differences may be that early-onset dementia is mainly caused by vascular comorbidities 34 that have a high prevalence rate among patients with hepatic, 35 intestinal, 36 and esophageal 37 dysfunction. These findings not only deepen the understanding in the etiological differences between early- and late-onset dementia but also may guide the secondary prevention for patients with different gastrointestinal conditions.…”
Section: Discussionmentioning
confidence: 99%